Exercise-induced muscle damage during the menstrual cycle: a systematic review and meta-analysis - Romero-Parra, N.; Cupeiro, R.; Alfaro-Magallanes, V. M.; Rael, B.; Rubio-Arias, J. Á.; Peinado, A. B.; Benito, P. J. (The Journal of Strength and Conditioning Research, 2021)
A strenuous bout of exercise could trigger damage of muscle tissue, and it is not clear how sex hormone fluctuations occurring during the menstrual cycle (MC) affect this response. The aims of this study were to systematically search and assess studies that have evaluated exercise-induced muscle damage (EIMD) in eumenorrheic women over the MC and to perform a meta-analysis to quantify which MC phases display the muscle damage response. The guidelines of the Preferred Reported Items for Systematic Reviews and Meta-Analysis were followed. A total of 19 articles were analyzed in the quantitative synthesis. Included studies examined EIMD in at least one phase of the following MC phases: early follicular phase (EFP), late follicular phase (LFP), or midluteal phase (MLP). The meta-analysis demonstrated differences between MC phases for delayed onset muscle soreness (DOMS) and strength loss (p < 0.05), whereas no differences were observed between MC phases for creatine kinase. The maximum mean differences between pre-excercise and post-exercise for DOMS were EFP: 6.57 (4.42, 8.71), LFP: 5.37 (2.10, 8.63), and MLP: 3.08 (2.22, 3.95), whereas for strength loss were EFP: -3.46 (-4.95, -1.98), LFP: -1.63 (-2.36, -0.89), and MLP: -0.72 (-1.07, -0.36) (p < 0.001). In conclusion, this meta-analysis suggests that hormone fluctuations throughout the MC affect EIMD in terms of DOMS and strength loss. Lower training loads or longer recovery periods could be considered in the EFP, when sex hormone concentrations are lower and women may be more vulnerable to muscle damage, whereas strength conditioning loads could be enhanced in the MLP.